ANALYSIS OF THEORETICAL AND PRACTICAL ASPECTS OF EXISTING METHODS IN IMPROVING STUDENTS' SPATIAL IMAGINATION IN DRAWING - Sultonova Gulshan (Bright Mind Publishing, 2025)
This article analyzes various methods and techniques aimed at improving the spatial imagination of students in the field of drawing from a theoretical and practical perspective. Spatial imagination is the process of a person's perception of the environment, imagination and thinking based on it. The development of spatial imagination in the field of drawing is important for students, as it affects their successful work in drawing, sketching, design and architectural design.
Keywords: Imagination, design, imagine, spatial imagination, axonometric projection.